Therapeutic Appraisal of Phalatrikadi Yoga with Lekhaniya Mahakashaya in Medoroga w.s.r. to Metabolic Syndrome: A Review. - Meenu; Chundawat, Anshu; Bihari, Krishana; Pandey, Ajai Kumar (International Research Journal of Ayurveda & Yoga, 2023)
Santarpanottha Vikaras (diseases due to excessive nutrition) are increasing in current era due to faulty lifestyle. Medodushti (disorders of fat metabolism) serves as one of the important etiological factors in most of these disorders including dyslipidaemia, obesity, metabolic syndrome etc. Obesity and Metabolic syndrome (MS) are interconnected disorders having global prevalence, which are associated with physiological, biochemical, clinical and metabolic abnormalities. Both disorders directly influence the risk of cardiovascular disease (CVD) and diabetes mellitus. MS is considered as a first order risk factor for atherothrombotic complications. Pharmacodynamic attributes i.e., Tikta, Katu, Kashaya Rasa, Laghu, Ruksha, Tikshna Guna and Ushna Veerya, Katu Vipaka have individual effect in obesity. Katu Vipaka is having more significant influence in producing Medohara, Lekhana and Karshana karma which is important for management of obesity. It will also help in selection of drugs for the management of Medoroga. Overall, the drugs having dominance Kaphavata shamaka, Dipana, Pachana (digestion), Srotoshodhana (channel cleansing), and Medohara (lipolytic) properties are found to be effective in the management of Medoroga w.s.r. Metabolic Syndrome. In this context, Ayurvedic formulation is selected to laid down an emphasis on its therapeutic potential based on Ayurvedic pharmacodynamic and contemporary work done by the researchers of biomedical sciences.